Green Antimicrobials - Felgueiras, Helena P. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the last couple of years, the awareness of climate change and high pollution levels have raised our sense of ecological responsibility. Pharmaceutical industries play a major role in these issues; as such, alternatives must be found. New environmentally friendly approaches to deal with the growing concern associated with antimicrobial-resistant bacteria are also in great demand. The excessive consumption and misuse of these agents have accelerated the rise of such pathogens responsible for compromising global health-not only the health of humans, but also the health of all living systems. Considering that our natural resources are in great danger, finding green and less environmentally impactful alternatives for fighting these resistant microbials is imperative. From green chemistries, natural extracts and waste products, the sources of these alternate antimicrobial agents can be immense, and their implications are of great impact for future generations.